Brain drain: what is the role of institutions? - Chen, Fanyu; Wong, Zi Wen Vivien; Law, Siong Hook (Springer Nature, 2024)
Brain drain is closely associated with human capital deficiencies and obstacles in economic development. In spite of its crucial economic implications, nations, especially the developing ones, have failed to prevent brain drain due to the focus on simple restrictive policies and the ignorance of institutional factors like weakly-enforced law and order, unfulfilled basic human rights, and others in preventing the outflow high skilled labor. Thus, this paper aims to investigate the impact of institutional quality on brain drain in 100 countries from 2007 to 2019, using system Generalized Method of Moments estimator to estimate the model involving data collected from the International Country Risk Guide, The Quality of Government Institute, and the World Bank. The empirical results indicated that quality of institutions is essential in preventing the outflow of highly skilled workers. It has become imperative for policy-makers in these countries to uphold and strengthen their nations’ institutional frameworks in order to retain and attract the valuable talents to stay on and reside in their own countries.